O organizing das artesãs de filé do Pontal da Barra, em Maceió/AL - Silva, Christianne Lobato Ramalho da (2017)
Handcraft is characterized as a practice in which individuals develop a modus operandi in their daily life that gives rise to events from and for their survival. These ways of making crafts makes possible the constitution of an organization to social subj